2012
DOI: 10.5944/rppc.vol.17.num.3.2012.11843
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation strategies as transdiagnostic processes: A closer look at the invariance of their form and function = Estrategias de regulación emocional como procesos transdiagnósticos: Una visión más detenida sobre la invarianza de su forma y función

Abstract: Recent investigations suggest that emotion regulation can be conceptualized as a transdiagnostic process (Kring & Sloan, 2010). Specifically, the habitual use of putatively maladaptive emotion regulation strategies (e.g., rumination, suppression), and the infrequent use of putatively adaptive strategies (e.g., acceptance, reappraisal) have been shown to predict various symptoms of psychopathology . However, little is known about the extent to which the different facets that constitute the process of implementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 86 publications
0
16
0
7
Order By: Relevance
“…Despite this growing evidence demonstrating the transdiagnostic nature of emotion dysregulation across disorders, it has been suggested that the next step in this area will be to investigate differential forms and functions of emotion regulation across affective problems (Aldao, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite this growing evidence demonstrating the transdiagnostic nature of emotion dysregulation across disorders, it has been suggested that the next step in this area will be to investigate differential forms and functions of emotion regulation across affective problems (Aldao, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, a growing body of evidence has begun to reveal the overlap among disorders, highlighting elements and processes that cut across disorders. For decades, emotion regulation has been explored as an important process in the onset and maintenance of various forms of psychopathology, yet only recently has it has been discussed as a transdiagnostic factor specifically (Aldao, 2012; Kring & Sloan, 2010). In the current article, we build upon this work and propose that emotion regulation be considered as a transdiagnostic factor that can be mapped directly onto the transdiagnostic framework proposed by the National Institutes of Mental Health (NIMH) —the Research Domain Criteria (RDoC).…”
mentioning
confidence: 99%
“…En esta línea, diversos estudios han encontrado similar relación con la sintomatología ansioso-depresiva Schafer, Naumann, Holmes, Tuschen-Caffier, y Samson, 2016). Estos hallazgos tienen importantes implicaciones para el conocimiento de la etiología de los trastornos de ansiedad y del estado de ánimo, poniendo de manifiesto el carácter transdiagnóstico de la regulación emocional (Aldao, 2012;. Respecto a la fiabilidad de la ERQ, nuestros resultados han mostrado una adecuada fiabilidad de la escala, con valores de alfa de Cronbach superiores a .84, lo que supone una mejora incremental de la fiabilidad comparado con los resultados de Cabello et al (2013) y Gross y John (2003).…”
Section: Discussionunclassified
“…La manera en que las personas regulan las emociones afecta a sus relaciones, su bienestar y percepción y experiencia del estrés (Gross, 2002;Lopes, Salovey, Côté, y Beers, 2005;), siendo la regulación emocional, junto a otros constructos transdiagnósticos primarios (Martínez-Vispo, Fernández del Río, López-Durán, y Becoña, 2016;Sánchez-Arribas, Chorot, Valiente, y Sandín, 2015), un concepto clave en el estudio de la psicopatología (Gil-Sanz et al, 2017;Jiménez, Orgambídez, y Pascual, 2015;Segura et al, 2017). Desde este marco, se han conceptualizado las estrategias de regulación emocional como adaptativas o desadaptativas en función de la relación que mantienen con los síntomas psicopatológicos (Aldao, 2012). Esta autora ha considerado como desadaptativas aquellas estrategias positivamente asociadas con los síntomas (p.ej., supresión, rumiación, preocupación, evitación) y adaptativas aquellas que correlacionan negativamente con los síntomas (p.ej., reevaluación, aceptación, resolución de problemas).…”
Section: Introductionunclassified
See 1 more Smart Citation